Early Phase of Primary Melanoma Growth from the Patient Point of view: A Prospective Cross Sectional Study on Melanoma over 1 mm in Thickness - Nausicaa Malissen; Safia Abed; Nicolas Macagno; Florent Amatore; Anderson Loundou; Florent Grange; Caroline Gaudy-Marqueste; Jean-Jacques Grob (Medical Journals Sweden, 2020)
A Nodular Pink Lesion with an Uncommon Diagnosis: A QuizMost melanomas are diagnosed by the patients themselves or by their partners or relatives; they alone can describe its history. We designed a prospective cross-sectional study to describe patients' perception of morphology, growth pattern and kinetics of their primary melanoma over 1 mm in thickness before resection. Patients were interviewed with a questionnaire, a grid representing 9 possible scenarios of melanoma growth, and a set of 87 photographs of potential aspects of melanomas and precursors. Most patients were able to describe the growth of their melanoma and select pictures representative of its successive aspects before resection. Among 453 patients, 60% reported a preexisting lesion present for years. Growth pattern scenarios concurred with tumor kinetics but with no statistical difference between nodular and superficial spreading subtypes. These subjective patient-reported indicators about melanoma growth over time could dynamically complement its objective pathological analysis otherwise static at a single time point.